THE INFLUENCE OF PRE-EMPLOYEMENT MEDICAL CHECK UP ON EMPLOYEE PERFORMANCE AT PT XYZ - Marcel Prathama; Sri Gustina; Meita Istianda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Purpose of this study aims to analyze the influence of pre-employment Medical Check-Up (MCU) results on employee performance at a Nickel Company (PT. XYZ) located in Morowali, Central Sulawesi. The pre-employment MCU is one of the initial selection processes intended to ensure the health condition of prospective employees before they are officially hired. Employee performance is measured based on periodic work evaluations conducted by direct supervisors, covering aspects such as productivity, punctuality, and work quality. The research methodology used is quantitative. Data were collected from 50 employees who had undergone all recruitment process including MCU pre-employment. Data analysis was performed using partial least squares (PLS) to determine the relationship between variables and the simultaneous influence of MCU results on employee performance.The findings from this study indicate a significant impact between pre-employment MCU results and employee performance. Employees with MCU results indicating good health conditions tend to have better performance compared to those with specific health records. Suggestions for MCU results can serve as an important indicator in the recruitment process for qualified employees.